Recurrence patterns following nephrectomy for renal cell carcinoma in a Danish nationwide cohort - Goran Bencina; Rolf Billeskov; Rasmine Bak; Ahmed Al‐Sabbagh; Julie Højgaard Pedersen; Marina Lunetcas; Emma Heeno; Sara Tolouee; Tuba Ashraf; Niels Fristrup; Nessn Azawi (BJUI Compass)
Abstract Objectives This study aimed to characterize the demographic and clinical features of patients with renal cell carcinoma (RCC) post‐surgery for localized or locally advanced disease in a national Danish cohort, with a specific focus on describing recurrence patterns in a subgroup aligned with the adjuvant KEYNOTE‐564 trial classification. Methods This was a retrospective analysis of the Danish Renal Cancer (DaRenCa) database. Eligible subjects were individuals with an RCC diagnosis between January 2014 and December 2017 who subsequently underwent radical or partial nephrectomy. Variables of interest were demographic and clinical characteristics, rates and sites of recurrence. Recurrence rates were also assessed in a subpopulation stratified using the risk classifications of the KEYNOTE‐564 trial. Results A total of 2164 RCC patients were identified. Most patients (84.8%) had non‐metastatic RCC (stage M0). A recurrence was observed in 250 of the M0 patients (13.6%). Patients with a recurrence were older, male, had a higher tumour stage, had undergone radical nephrectomy and had a higher Leibovich score. The majority (74.8%) of M0 patients had recurrence at distant metastatic sites. A total of 392 patients were stratified by the KEYNOTE‐564 risk classification: 335 intermediate‐high risk, 17 high risk and 40 M1 NED (metastatic with no evidence of disease). Recurrence was observed in 37.0%, 88.2% and 27.5% of these risk groups, respectively. Conclusions This study elucidates the rates and determinants of post‐surgical RCC recurrence in Denmark, underscoring the potential of adjuvant immunotherapy in refining therapeutic strategies, identifying suitable beneficiaries and minimizing overtreatment risks in RCC care.